Exceeding 30 % External Quantum Efficiency in Non‐doped OLEDs Utilizing Solution Processable TADF Emitters with High Horizontal Dipole Orientation via Anchoring Strategy. (12th October 2022) - Zhao, Guimin; Liu, Dan; Wang, Panpan; Huang, Xinping; Chen, Haowen; Zhang, Yuewei; Zhang, Dongdong; Jiang, Wei; Sun, Yueming; Duan, Lian
Abstract: Strategies to enhance the ratio of the molecular horizontal emitting dipole orientation (Θ∥ ) for thermally activated delayed fluorescence (TADF) emitters have unlocked the full potential of efficiencies for the evaporated devices, which, however, remain elusive for the solution‐processed ones. Here, a strategic molecular design for solution processable TADF emitters featuring high Θ∥ s is proposed by attaching flexible chains ended with bipolar 9, 9′‐spirobi[fluorene] subunits as anchoring groups onto TADF emitting core. It's unveiled that the anchoring groups not only enhance the horizontal orientation via enlarging molecular planarity, but also benefit the high photoluminescence in pristine films. The corresponding non‐doped solution processable OLEDs substantiate an unprecedented maximum external quantum efficiency (EQEmax )>30 %. Meanwhile, combining these compounds as TADF sensitizers, and multiple resonance final emitter, solution‐processed OLEDs achieve an EQEmax of 25.6 % with a narrow full width at half maximum of 29 nm. Abstract : An anchoring strategy was firstly proposed to generate solution processable TADF emitters from isotropic orientation to horizontal one by attaching bipolar 9, 9′‐spirobi[fluorene] subunits as anchoring groups onto TADF emitting core via flexible chains. With outstanding characteristics in pristine films, unprecedented EQEmax s of 30.6 % and 25.6 % were achieved for solution processable non‐doped OLEDs and TSF OLEDs, respectively.